Analisis Eksploratif Strategi Manajerial Sumber Daya Manusia Untuk Meningkatkan Produktivitas Kerja Di Rumah Sakit Tentara Tk. IV Atambua: Pendekatan Mix Method - Bambang Sugiyarto; Dasrun Hidayat; Kahar Mulyani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The background of this study is based on the importance of human resource (HR) managerial strategies in enhancing the performance of healthcare workers. The productivity of healthcare workers is a crucial factor in ensuring the quality of hospital services, especially in military institutions such as Military Hospital Level IV Atambua, which face challenges such as high discipline, work pressure, and limited facilities. The aim to explore the managerial HR strategies that influence the productivity of healthcare workers, such as internal challenges, applied managerial strategies, management critique strategies, incentives, appreciation, work facilities, and work environment. The research design using an exploratory mixed-method approach. Data were collected through in-depth interviews and questionnaires with healthcare workers and management at the IV Army Hospital in Atambua. The analysis was then conducted thematically and quantitative data processed to identify patterns of managerial strategies and their impact on productivity. The findings shows that the human resource managerial strategy has been implemented through routine training, periodic evaluations, and a job rotation system. This strategy is considered effective in enhancing the skills of healthcare workers, although the distribution of training is not yet evenly distributed across all professions due to internal challenges. On the other hand, hospitals are also trying to provide supporting facilities, but still face constraints of limited medical equipment and comfortable work facilities. The system of incentives and appreciation is still lacking in the hospital environment. However, the aspects of communication and management involvement are still perceived to be suboptimal. The study concludes indicates a strong correlation between human resource management strategies and job satisfaction among healthcare workers, which ultimately impacts work productivity. Enhancing the incentive system, welfare programs, and internal communication are key factors in strengthening the performance of healthcare workers in military hospitals.